Posterior Cranial Vault Distraction in the Treatment of Shunt-Induced Craniosynostosis. Issue 1 (January 2015) - Bhadkamkar, Mohin A.; Albright, Steven B.; Wolfswinkel, Erik M.; Bollo, Robert; Buchanan, Edward P.
<x xml:space="preserve">Abstract</x> Abstract Cerebrospinal fluid shunt placement is the most common surgical intervention for hydrocephalus. In rare cases, cerebrospinal fluid shunting has been associated with the development of secondary craniosynostosis. Posterior cranial vault distraction osteogenesis is an emerging technique used for the treatment of craniosynostosis. Posterior vault distraction allows greater intracranial volume expansion than do techniques that address the anterior cranium. We present a patient with shunt-induced multisuture craniosynostosis with delayed presentation. She was effectively treated with posterior cranial vault distraction and preservation of her ventriculoperitoneal shunt. This unique case demonstrates the safety and utility of this procedure for complex craniocerebral disproportion.